“Vuestra vertud me vala, Gloriosa, en mi exida”: función del culto mariano e ideología de cruzada en el Poema de Mio Cid - Riva, Fernando (2011)
This paper, inserted in the framework of the Cid studies, aims to identify the existence of a strong presence of the cult to the Virgin Mary in the Poema de Mio Cid (PMC), which articulates the battle scenes of the poem and is presented as a projection of Castile’s expansionist intentions in the context of the wars of Spanish reconquest. Likewise, it seeks to demonstrate the strong French influence in the Marian cult, which can be seen throughout the text, and its adoption by the religious Peninsula, particularly in relation to the ideology of crusade that matches the changing notion of reconquest and constitutes one of the main motives of the poem.